On the wear and corrosion of plasma nitrided AISI H13 - Fernandes, F. A. P.; Heck, S. C.; Picone, C. A. [UNESP]; Casteletti, L. C. (Elsevier B.V., 2020)
Tool steels are applied in a variety of industrial operations providing a good balance of properties. Surface engineering has the potential to improve productivity and further extend the lifetime of metallic components. In the present work plasma nitriding is applied to the hot work AISI H13 tool steel to improve wear and corrosion characteristics. The steel was nitrided in the tempered condition at three different temperatures and pressures for 5 h of duration. At 450 degrees C of nitriding temperature mainly a diffusion zone is observed while a compound layer is produced at 550 and 650 degrees C. Both surface and bulk hardness decrease as nitriding temperature is increased. Xray diffraction indicates that a mixture of both epsilon and gamma' iron nitrides is produced in all cases. The content of epsilon-nitride appears to decrease with temperature while gamma'-nitride and CrN increase. Working pressure does not lead to significant alterations in phase proportion, hardness and wear resistance after plasma nitriding at a given temperature. However, increasing processing temperature, from 450 to 650 degrees C, reduces the wear coefficient from 1.19.10(-7) to 7.06.10(-8) mm(3)/N.m, respectively, while from the base steel such coefficients are in the order of 10(-5) mm(3)/N.m. Regarding the corrosion behavior, plasma nitriding at 450 and 550 degrees C yields higher corrosion potentials, lower current densities and an extensive passivation range, while the tempered substrate, irrespective the condition, exhibits no passivation. From the wear and corrosion perspective it is concluded that plasma nitriding at 450 or 550 degrees C leads to better corrosion properties while nitriding at 650 degrees C yields a better wear performance.
Keywords: Plasma nitriding; Tool steels; AISI H13; Wear; Corrosion